Prevalence of obesity and overweight among the college students of the campus of health sciences of the university of Pernambuco - Falcão, Viviane Tannuri Ferreira Lima; Miranda, Marcelino Leite de; Silva, Roseane Maria Cavalcanti (Rev Rene, 2007)
The high prevalence of overweight and obesity is presented, currently, as one of the most important problems of public health. Objective: first to calculate the prevalence of obesity and overweight in the adolescent college students of the campus of health and sciences of the University of PE; to identify them according to: sex, age, monthly familiar income and life style. Methods: epidemiologic study and description, quantitative transversal line with characteristics. The population who took part in the study was constituted by 5680 college students aged between 18 and 22. Results: the prevalence of overweight and obesity was 6.2% in the men and in the women 4%. 41.7% of the university students said to have at least one relative with the problem of obesity. 62.5% were used to consuming balanced meals. The sedentarism is present in 41, 2% of the adolescents. Conclusion: obesity is present in 1,2% of the 240 college students and that the overweight condition occurs in 9,2%, this clinical condition reaches global epidemic ratios and it is present in all the social-economic classes and ages.